ANALYSIS OF CONFIGURATION OF PILE GROUP ON SUPPORTING CAPACITY AND PILE EFFICIENCY IN TANJUNG BALAI FLAT CONSTRUCTION (Jurnal Teknik Sipil dan Arsitektur, 2024)
In the TanjungBalai Flats creation project, the inspiration used is a mini pile basis with a set pile device. The organization pile device on the inspiration withinside the creation of this flat is deliberate to have a exclusive wide variety of piles, particularly piles, 3 piles, 4 piles. Therefore, on this look at diverse pile configurations might be completed with the aid of using modelling exclusive configurations with the equal wide variety of piles as the development of this flat. Furthermore, the sporting ability and performance values might be as compared that is the first-class value. Calculations on this look at had been the usage of the direct method (Direct One) and the pile performance component for the evaluation of the pile bearing ability. The calculation is accomplished primarily based totally at the soil statistics received withinside the shape of sondir statistics. The significance of the pile performance value (Eg) in a pile organization is encouraged with the aid of using the pile arrangement, the wide variety of rows, the wide variety of piles in a single row, and the pile distance inclusive of the three pile configuration of the project (V3) has an performance value (Eg) = 0,817 and (Qg) = 205.27 whilst the evaluation of the layout pile (V3-1) has an performance value (Eg) = 0.861 and (Qg) = 216.32. From the calculation effects it could be concluded that the affect of organization pile configuration at the pile bearing ability is encouraged with the aid of using the significance of the pile performance (Eg), the more the pile performance, the more the sporting ability.